(untitled) - Davidsson, Per (Boston, 2004)
The book is targeted at doctoral students and other relative newcomers to the field of entrepreneurship research. However, taking a fresh, reflective perspective and looking beyond research conventions, it should provide potential for inspiration and food for thought also for experienced entrepreneurship researchers.
Keywords: Doanh nhân,Entrepreneurship; Nghiên cứu,Research